Can Sericin Prove Useful as a Pleurodesis Agent or Tissue Glue? - Yazicioglu, Alkin; Demirag, Funda; Alici, Ibrahim Onur; Yekeler, Erdal; Karaoglanoglu, Nurettin (The Thoracic and Cardiovascular Surgeon, 2017)
Background Sericin is a natural, gum-like, macromolecule protein, synthesized from silkworms for the formation of cocoon shells. The aim of the present study is to describe the effects of sericin when used for pleurodesis and/or as tissue glue.Methods Adult, male, 12-week-old Wistar albino rats, weighing 257 to 395 g were used in the present study (n = 12). The animals were randomly divided into two equal groups as the sericin and the control group. After intramuscular administration of the anesthetic agent, the rats were intubated and mechanically ventilated. A left thoracotomy was performed and 30 mg sericin powder was instilled into the thoraxes of the sericin group. The remaining rats were allocated to a sham thoracotomy group. The animals were housed in individual cages, fed ad-libitum, and sacrificed 8 days after. After sacrifice, the left hemithoraxes were removed en bloc and underwent histopathologic examination.Results Masson trichrome staining was applied on the visceral pleura sections of all the animals. Each animal specimen (n = 6, 100%) in the control group showed minimal collagen deposition, while only one rat (16.67%) in the sericin group had minimal collagen deposition. However, in the sericin group, five animals (83.33%) showed dense collagen deposition, fibroblastic activity, and fibrosis. According to the test method, independent t-test, developing fibroblastic activity and fibrosis are statistically significant between the two groups (p < 0.01). There were no foreign-body reactions and no evidence of biological glue on the specimens in the sericin group. The rats in the sericin group had lower inflammatory reactions compared with those in the control group. Emphysema was observed in two rats (33.33%) in the sericin group and in four rats (66.67%) in the control group. Therefore, sericin was found to be associated with an increase in fibroblastic activity and fibrosis in visceral pleura without exerting any adverse effect on the lung parenchyma.Conclusion Sericin is a new and researchable protein for chest diseases and thoracic surgery. To develop an effect of dense collagen deposition, fibroblastic activity, and fibrosis in the visceral pleura, without significant adverse effects, is remarkable. Therefore, sericin may be useful as a pleurodesis agent or natural biological glue in the future. Sericin treatment can add value to the disciplines of pulmonology and thoracic surgery.
Keywords: sericin; gum-like; fibrosis; fibroblastic; pleurodesis